11t-10=4t-5

Simple and best practice solution for 11t-10=4t-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11t-10=4t-5 equation:


Simplifying
11t + -10 = 4t + -5

Reorder the terms:
-10 + 11t = 4t + -5

Reorder the terms:
-10 + 11t = -5 + 4t

Solving
-10 + 11t = -5 + 4t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-4t' to each side of the equation.
-10 + 11t + -4t = -5 + 4t + -4t

Combine like terms: 11t + -4t = 7t
-10 + 7t = -5 + 4t + -4t

Combine like terms: 4t + -4t = 0
-10 + 7t = -5 + 0
-10 + 7t = -5

Add '10' to each side of the equation.
-10 + 10 + 7t = -5 + 10

Combine like terms: -10 + 10 = 0
0 + 7t = -5 + 10
7t = -5 + 10

Combine like terms: -5 + 10 = 5
7t = 5

Divide each side by '7'.
t = 0.7142857143

Simplifying
t = 0.7142857143

See similar equations:

| 9.8m+20=2m | | 9.8m-10=m*5 | | 9.8-10=m*5m | | 9.8-10=m*5 | | 4u^2-6=5u | | 12x-8=4x+3 | | 9.8m-20=2m | | 3x+x=540 | | x^2+11x=15 | | 3x+y=540 | | 54-4x=23x+24 | | -103-7x=10+16 | | 6x+13=147-10x | | 6x+13=147-10 | | 2v^2+7v=-5 | | t+1+2+3+4+5+6+7+8+9=123456789 | | 114-6x=9x+4 | | 3x+9x+6x=396x | | -3x+(7ab-4)-5x-3b-(3a+22a-x)= | | 132-5x=31x+20 | | 13-8x=213-43x | | 2k+3= | | 41=15+13(9m-16) | | 41=15+13(19m-16) | | 2a+3=2a+4 | | log(x-2)+log(2-x)=1 | | 3lnx+ln(9-(8x^3))=0 | | 210S+265E=4485 | | 3lnx+ln(9-8x^3)=0 | | 3o+13=23-2o | | 15-(2x+3)=3-3X | | 23-3x=6x+19 |

Equations solver categories